Morphology Of Fruits And Seeds Of Chaenomeles Species - Gulamkhodjaeva Shakhnoza Fakhritdinovna; Turatov Muzaffar Nuralievich (Zien Journals, 2022)
The article presents the results of the study of fruit and seed morphology of ornamental Japanese quince or Japanese quince (Chaenomeles japonica (Thunb)Lindl.), Mauley's chaenomeles (Chaenomeles Maulei (Mast.) Schneid.). The diameter and weight of fruits and seeds were determined.
Keywords: Fruit; bush; species; flower